2013
DOI: 10.1111/jrh.12014
|View full text |Cite
|
Sign up to set email alerts
|

Larger Regional and Rural Areas in Victoria, Australia, Experience More Alcohol‐Related Injury Presentations at Emergency Departments

Abstract: Regional and coastal areas experience increased alcohol-related injury rates. The causes of this have yet to be investigated and future research is required to determine why and what interventions may be most effective at reducing these harms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…Finally, the lower subjective well‐being of this sample is consistent with previous research which reported lower subjective well‐being in rural and regional drug users [23]. Indeed, rurality is predictive of a range of AOD problems [35–37], and issues such as lack of access to treatment services, higher rates of unemployment and social isolation, these factors may account for some of the differences observed in this group compared with those accessed in previous research.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, the lower subjective well‐being of this sample is consistent with previous research which reported lower subjective well‐being in rural and regional drug users [23]. Indeed, rurality is predictive of a range of AOD problems [35–37], and issues such as lack of access to treatment services, higher rates of unemployment and social isolation, these factors may account for some of the differences observed in this group compared with those accessed in previous research.…”
Section: Discussionsupporting
confidence: 89%
“…It is interesting to note that higher alcohol consumption in these two seasons is mentioned in some other studies as well (18, 19). On one hand, noncommercial alcoholic beverage production, sale and consumption has no seasonal rhythm; on the other, it seems that alcohol users in our study are occasional rather than regular users.…”
Section: Discussionsupporting
confidence: 64%
“…The ED data comes from the Non-Admitted Patient Emergency Department Care (NAPEDC) database. This data captures a broad spectrum of alcohol-related injuries (e.g., minor fractures from falls and assaults), many of which are unlikely to be recorded in police data [ 17 , 18 ], and are often not serious enough to result in admission to a hospital ward, but occur relatively frequently among high-risk population groups [ 19 ]. The ED data will include 28 Queensland hospitals from January 2005 onwards.…”
Section: Methodsmentioning
confidence: 99%